'A Conference That Didn't': African Diaspora Studies and an episode in anthropology's identity politics of representation. (December 2018) - Yelvington, Kevin A
In 1968, the Social Science Research Council of the United States established the Committee on Afro-American Societies and Cultures which lasted until 1975 and which was initially chaired by the anthropologist Sidney W Mintz. In April, 1970, the committee held a conference on 'Continuities and Discontinuities in Afro-American Societies and Culture' at the University of the West Indies in Mona, Jamaica. The conference occurred in the context of civil rights struggles and the prominence of the Black Power movement in the United States, the near-simultaneous rise of the Black Power movement in Jamaica, Trinidad and Tobago, and elsewhere in the Caribbean, and on the heels of protests by black and African scholars and students at the African Studies Association meetings in Montreal in 1969, and similar protests at other scholarly venues. A number of prominent white Caribbeanist anthropologists and other social scientists were invited to present papers at the Social Science Research Council conference. When black academics, such as the anthropologist St Clair Drake and the sociologist Joyce A Ladner, were invited, seemingly as an afterthought, they refused to participate, citing the lack of representation of scholars of colour on the committee and in the conference program. And at the conference itself, there were subtle conflicts and misunderstandings over styles of presentation and argumentation. This article develops a theoretical model appropriate for the history of science to illustrate anthropology's contested identity politics of representation.